Potassium iodide in dermatology: A 19th century drug for the 21st century—uses, pharmacology, adverse effects, and contraindications - Sterling, J.Barton; Heymann, Warren R. (Journal of the American Academy of Dermatology, 2000)
Potassium iodide (KI) is a useful drug in the dermatologic armamentarium. It is successfully used for inflammatory dermatoses, most notably erythema nodosum, subacute nodular migratory panniculitis, nodular vasculitis, erythema multiforme, and Sweet's syndrome. KI is also successfully used for cutaneous and lymphocutaneous sporotrichosis. The precise mechanism by which KI acts is unknown. Although many minor side effects are common with this drug, major side effects can occur in pregnant patients and those with a history of kidney or thyroid disease. This article reviews the pharmacology, mechanism of action, indications, contraindications, and adverse effects of KI as a therapeutic agent. (J Am Acad Dermatol 2000;43:691-7.)